A crowning moment for HMRC?. (2nd January 2020) - Bernstein, Adam
Abstract : New legislation coming into effect in 2020 means that, if a business fails, HMRC will take precedence in the line of creditors pursuing owed monies. This may mean a rise in the costs of borrowing and investment. Adam Bernstein discusses the potential impact of this on the care industry